The Role of Intercultural Sensitivity and Organizational Climate on Innovative Work Behavior - Kania, Okky; Rostiana (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2026)
In the context of a nation such as Indonesia, Innovative Work Behavior (IWB)—defined as employees’ deliberate creation, promotion, and implementation of novel ideas, processes, or products intended to benefit the organization—assumes particularly high strategic relevance. This study examines the simultaneous effects of intercultural sensitivity and organizational climate on innovative work behavior (IWB), a relationship rarely explored in the Indonesian context. Using a cross-sectional quantitative design, data were collected from 102 employees of a multinational IT company. Measurement instruments included the Innovative Work Behavior Scale (IWBS), Intercultural Sensitivity Scale (ISS), and Organizational Climate Scale (CLIOR). Results show that intercultural sensitivity (t = 2.509) and organizational climate (t = 4.231) significantly predict IWB, jointly explaining 39.4% of its variance. This moderate level of explanation indicates that while these factors play an important role in fostering innovation, other variables may also contribute. The findings suggest that employees with higher intercultural sensitivity tend to generate and implement ideas more effectively, especially when supported by a positive organizational climate. The study contributes theoretically by integrating individual and organizational determinants of innovation into a unified framework, and practically by offering insights for building culturally inclusive workplaces that enhance creativity. This study fills the gap by examining the joint effect of intercultural sensitivity and organizational climate in a multicultural IT setting, an area less explored in prior studies.